The employer branding effect on employee commitment - Silva, Francisco Pratas e Sousa Tavares da (2021)
Creating and developing a strong employer brand is becoming one of the most crucial challenges for organizations to strive. Many studies focus on its impact on the companies’ attractiveness and retention dimensions. This study is aimed towards another dimension, the impact on employees’ commitment. This research has a theoretical and a practical component, in the form of a questionnaire. The questionnaire was distributed and completed by 152 participants (N=152). Employer branding was measured using a scale developed by Tanwar and Prasad in 2017, that divides it into 5 areas: healthy work atmosphere; training and development; work-life balance; ethics and corporate and social responsibility; compensation and benefits. To assess employee commitment, the Three Component Model created by Meyer and Allen in 1991, in which commitment is separated into affective commitment, normative commitment and continuance commitment. The results achieved were that from those employer branding variables, healthy work atmosphere, and ethics and corporate social responsibility help explaining affective commitment. Normative commitment is only explained by healthy work atmosphere, while none of the above employer branding dimensions help understanding continuance commitment.